In Vivo Imaging: Molecular Engineering of an Organic NIR‐II Fluorophore with Aggregation‐Induced Emission Characteristics for In Vivo Imaging (Small 20/2019). Issue 20 (17th May 2019) - Wu, Wei; Yang, Yanqing; Yang, Yang; Yang, Yuming; Zhang, Kaiyuan; Guo, Li; Ge, Hongfei; Chen, Xiaowei; Liu, Jie; Feng, Hua
Abstract : In article number1805549, Xiaowei Chen, Jie Liu, Hua Feng, and co‐workers prepare a new aggregation‐induced emission (AIE) luminogen (AIEgen) through molecular engineering by varying a single atom from sulfur to selenium. The resultant AIE nanoparticles have an emission tail extending to 1200 nm with a high quantum yield. The light from these nanoparticles allow for clear vessel imaging.